Alzheimer's Disease - Wisniewski, Thomas (Exon Publications, 2019)
Alzheimer's disease (AD) is the most common cause of dementia. With the increasing average age of humans worldwide, the total number of people with dementia is projected to reach 82 million by 2030 and 152 million by 2050. No effective pharmaceutical agents exist to halt or slow down the disease progression. Hence, there is a tremendous imperative to gain a better understanding of the pathogenesis of AD and to develop effective treatments. This book brings together an international team of experts to provide a comprehensive and up-to-date overview of AD. The most current information on several critical aspects of AD are presented, providing the readers with a broad picture of the underlying neuropathology, genetics, proteomics, risk factors, novel biomarkers, and potential interventions. Chapters 1-5 discuss the underlying AD pathogenesis using genomic and proteomic approaches, linking diverse pathways that can lead to complex metabolic dysfunction. Chapter 6 reviews the potential role of trace metals in AD, while Chapter 7 examines the diversity of Aβ species involved in AD pathology. Chapter 8 discusses the contributions of white matter degeneration in AD. Chapter 9 examines the potential intriguing role of the brain-gut-microbiota axis in mediating AD. Chapters 10 and 11 discuss potential biomarkers for AD, such as deficits in ocular exploration and early language impairments, respectively. Chapters 12-15 examine possible novel preventative and/or therapeutic methodologies such as exercise, optimizing depression therapy, and diverse psychosocial interventions. The book will be of value to clinicians and health professionals caring for patients with AD, and will provide a comprehensive and thought-provoking introduction to young investigators interested in translational aspects of the AD and related dementias.